Nixon's desperate attempt to fight inflation - Dietrich Kebschull; Carsten R. Moser (Intereconomics, 1971)
Because of continuing Inflation and rising unemployment, Americans were beginning to feel rather frustrated with the Nlxon Administration for their non-actions on the economic front. As an answer to this growing feeling of anxiety the US-President introduced an economic programme which has caused quite a stir in the USA as well as abroad. The author's intent is to discuss the national and International effects the Nlxon programme will probably have.
Keywords: 330; International monetary policy